Design and Validation of a Wayang Drama Structure Teaching Module Based on the ADDIE Framework - Alfian Anggoro Mukti; Eko Gunawan; Husein Erwinsyah; Aminatul Nur Afifah (Javanologi: International Journal of Javanese Studies, 2025)
The Wayang Drama Structure course is a new course that requires more references in the teaching process. Therefore, this study aims to produce a teaching module for the Wayang Drama Structure course. This research was conducted by applying the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research and development model. Data collection was carried out using questionnaires. The questionnaires were filled out by research subjects consisting of subject matter experts, media experts, and students. The data obtained through the questionnaires was then analyzed using quantitative descriptive analysis. The results showed that the teaching module that was developed met the feasibility requirements. The material feasibility data obtained was 80% in the good category, the media feasibility level was 88% in the very good category, and the small group trial feasibility level was 82.68% in the very good category. Thus, this teaching module draft is ready and very feasible to be used for learning in the Wayang Drama Structure course.